Pengaruh Disiplin Kerja dan Motivasi Kerja terhadap Kinerja Karyawan pada PT XYZ - Kartika Herdianty; Purwatiningsih, Purwatiningsih; Ratih Setyo Rini (Jurnal Manajemen Kreatif dan Inovasi, 2024)
PT XYZ is a company with a wide network and services for the community. To achieve success in a company, good performance is required, which is based on work discipline and work motivation. The aim of the research is to determine the influence of work discipline and work motivation on employee performance at PT XYZ. This research uses a quantitative approach with nonprobability sampling data collection techniques, namely saturated sampling. The population in this study consisted of all PT XYZ employees, with a total sample of 47 respondents. Primary data was collected using questionnaires in Likert scale units. Data processing uses SPSS 25 software for the tests used are data quality test, classical assumption test, multiple linear regression analysis, hypothesis testing, and coefficient of determination. The results of this research are proven by the results of the partial test (T) on the work discipline variable (X1) showing that there is a positive and significant influence on the employee performance variable (Y) and on the work motivation variable (X2) it also shows that there is a positive and significant influence on the variable employee performance (Y), while the results of the simultaneous test research (F) show that there is a positive and significant influence of the variables work discipline (X1) and work motivation (X2) on employee performance (Y).